Measuring the Effect of Problem Based Learning With Instructional Video on Primary School Students' Problem Solving Skills Development - Fitriati, Fitriati; Rahmi, Rahmi; Novita, Rita; Salmina, MIK; Sari, Intan Kemala; Nasriadi, Ahmad; Muzakir, Ully; Fajri, Nurul (Teunuleh Publisher, 2023)
This study aims to analyse the efficacy of instructional video through problem-based learning model in developing problem-solving skills among primary school students. This research integrated in video instructional material related to statistics topics